Biological and Technological Indicators of Partenoklons - Erimmatovna, Abdrimova Gulbaxor; Rano, Kamalova (American Journal of Biology and Natural Sciences, 2025)
The article defines the biological and technological indicators of parthenoklones. According to the analysis results, the yield of parthenogenetic caterpillars varies within 75.33-91.33%, which indicates a low control compared to the bisexual SANIISH-30 breed; the technological indicators of parthenoklones are quite high. The metric number of the 5140pk clone reaches 3991 units, and the A-218pk - 3827 units. The cocoon unwinding of the A=238 pc clone is 85.88%, and the A-261 clone is 86.54%. The silk yield of A-153pk is 48.81%, and A-261pk is 49.7%.